A common mechanism of detoxification for lambda-cyhalothrin and abamectin in Cydia pomonella - Di Ju; Chao Hu; Peirong Li; Ping Gao; Yuting Li; Xueqing Yang (CABI Agriculture and Bioscience)
Abstract Background The primary method utilized by orchard owners to combat Cydia pomonella is the application of various chemical insecticides. However, this has resulted in the development of resistance. The resistance mechanisms to insecticides from different chemical classes are diverse but interconnected. Therefore, it is crucial to comprehend the commonalities in these mechanisms to effectively develop strategies for managing resistance. Materials and methods To determine whether target-site insensitivity to LCT and AM plays a role in resistance, the sequences of voltage-gated sodium channel (VGSC) and glutamate-gated chloride channel (GluCl) containing the mutation domains were detected. To validate whether similar mechanisms were involved in the detoxification process of lambda-cyhalothrin (LCT) and abamectin (AM) at sublethal doses (specifically LD10 and LD30), cytochrome P450 monooxygenases (P450), glutathione S-transferases (GST), and carboxylesterases (CarE) activities were evaluated after insecticides exposure; synergistic experiments were conducted using piperonyl butoxide (PBO), diethyl maleate (DEM), and triphenyl phosphate (TPP) as inhibitors of P450, GST, and CarE respectively. RNA-sequencing (RNA-Seq) was performed to compare the expression levels of detoxification-related genes between susceptible (SS) and resistant strains. Results The best known target-site mutations caused by LCT and AM, including L1014F in VGSC and V263I, A309V, I321T, and G326E in GluCl were not occurred. We observed that PBO had a strong synergistic effect on LCT and AM, while DEM on LCT. The activities of detoxification enzymes increased after insecticide exposures, indicating that the detoxification of LCT was primarily carried out by P450 and CarE enzymes, while P450 and GST enzymes played a major role in the detoxification of AM. A total of 72 P450 genes and 75 CarE genes were identified in the C. pomonella transcriptome, with 43 of these genes (including 11 P450, 3 GST, 10 CarE, 11 ABC transporters, and 8 UDP-glycosyl transferases) being over-expressed in response to both insecticides Interestingly, ABC transporters were predominantly induced by AM treatment, while GST showed higher induction levels with LCT treatment. Furthermore, LCT-resistant strains of C. pomonella exhibited higher levels of induction of detoxification-related genes compared to susceptible strains. Conclusion The up-regulation of these detoxification genes is a common metabolic mechanism employed by C. pomonella to counteract the effects of insecticides, although the extent of gene expression change varies depending on the specific insecticide.